Influence of pedal arch quality on 5-year survival and limb salvage in patients with diabetic foot ulcers undergoing peripheral angiography. (October 2022) - Troisi, Nicola; Guidotti, Azzurra; Turini, Filippo; Lombardi, Renzo; Falciani, Francesca; Baggiore, Cristiana; Michelagnoli, Stefano; Chisci, Emiliano
Introduction: The aim of this study was to evaluate the influence of pedal arch quality on 5-year survival and limb salvage in diabetic patients with foot wounds undergoing peripheral angiography. Methods: Between January 2014 and December 2014, 153 diabetic patients with foot wounds underwent peripheral angiography. Final foot angiograms were used to allocate patients according to pedal arch: complete pedal arch (CPA), incomplete pedal arch (IPA), and absent pedal arch (APA). Five-year survival and limb salvage rates were analyzed with Kaplan–Meier curves and compared by means of Gehan–Breslow–Wilcoxon test. Associations of patient and procedure variables with overall survival and limb salvage outcomes were sought with univariate and multivariate analyses. Results: A below-the-knee (BTK) artery was the target vessel in 80 cases (52.3%). Five-year Kaplan–Meier rates of survival were similar in all groups ( p = 0.1): CPA 30%, IPA 27.5%, and APA 26.4%. Five-year limb salvage rates were significantly better in patients with CPA/IPA ( p < 0.001): CPA 95.1%, IPA 94.3%, and APA 67.3%. In the whole population study, multivariate analysis showed significant association of smoking ( p = 0.01), chronic renal failure ( p = 0.02), and severity of foot wounds ( p < 0.001) with survival. Coronary artery disease ( p = 0.03), severity of foot wounds ( p = 0.001), and pedal arch status ( p = 0.05) showed strong association with limb salvage. Conclusions: Pedal arch quality significantly affected limb salvage but not survival at 5 years in patients with diabetic foot ulcers. Smoking, chronic renal failure, and severity of foot wounds affected overall survival, whilst coronary artery disease, and severity of foot wounds limb salvage.